Expression Pattern of CD34 at the Maternal–Foetal Interface During Pregnancy in Pigs. Issue 5 (15th March 2013) - Hong, L; Hou, C; Li, X; Li, C; Yu, M
Contents: The pig exhibits a non‐invasive, epitheliochorial placentation. Adhesion molecules are indispensable for successful implantation and establishment of placentation. CD34 is an adhesion molecule belonging to the immunoglobulin superfamily (IgSF). To take the first step to investigate the role of CD34 in placentation, we examined the expression pattern of CD34 at the maternal–foetal interface in Yorkshire gilts on days 15, 26, 50 or 95 and in Meishan gilts on days 26, 50 or 95 of pregnancy (n = 3 gilts/breed/day of pregnancy) by immunohistochemical technique. The CD34‐positive signals were detected in uterine luminal epithelium and trophectoderm in Yorkshire pigs; the staining for CD34 was located in trophectoderm but barely detectable at the uterine luminal epithelium on day 15 of pregnancy. Then, the expression of CD34 increased dramatically in both the uterine luminal epithelium and trophectoderm by day 26, and weak staining intensity was observed at the maternal–foetal interface on days 50 and 95 of pregnancy. The expression pattern of CD34 in Meishan pigs is similar to that in Yorkshire pigs except that only a few positive signals were observed at the luminal epithelium on day 26 of pregnancy. These results suggest that CD34 may be involved in mediating the cell‐to‐cell adhesion between trophectoderm and the luminal epithelial cells during early pregnancy in pigs.